Interpretação e mutação constitucional - Daniele, Anna Luisa Walter de Santana (2008)
This work has the objective to discuss the constitutional interpretation as a factor of constitutional rules actualization. The theme is justified by successives constitutional amendments that cause loss of authority and prestige to the Constitution. The constitutional change has the objective to fit social reality to the constitutional rules. The Constitutional interpretation, with principles aid, presents some specifities due to own characteristics of the constitutional rules. Its open character rules allow an interpretation that actualizes Constitution without changes in its text. The species of constitutional changes are: legislative, administrative, judicial and resulting from customs